Effect of match play on groin injury risk factors in young soccer players - Paul, D.; Whiteley, R.; Marques, J.; Nassis, G. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The propensity of groin injuries (1.0-1.1 per 1000 playing hours, accounting for 11 to 16% of all soccer injuries) among soccer players has stimulated much interest in the research and applied domain. Risk factors include age, high level of play, previous injury, amongst others (Engebretsen et al., 2010). However, there is limited data pertaining to the effects of match load on groin injury risk factors such as strength and flexibility. Therefore, the aim of present study was to 1) determine the reliability of hip flexibility and strength measures, and 2) identify the effects match play load has on these measures. Method: Sixteen elite national level youth team soccer players (15-17 years old) performed strength (adduction and abduction) and flexibility (bent knee fall out test) measures on 2 separate occasions 24hr apart. Reliability was evaluated with the Intraclass Correlation Coefficient (ICC). The same players repeated these tests ~9hrs before and 14hrs after an international friendly match. Minutes played x rate of perceived exertion was used to quantify match play load (Foster et al., 1996). Statistical analysis was performed with paired T-test. Results: A moderate ICC was reported for right (0.610) and left leg (0.551) flexibility measures. A low ICC was found for adductor and abductor strength for both legs. Left leg flexibility deteriorated significantly from before to after the match (pre: 16.8±5.3, post: 19.8±5.1cm, mean±SD, p=0.01). A similar trend was shown for the right leg (pre: 17.3±5.1, post: 18.4±5.7cm, p=0.09). An exponential relationship was found between match load and changes in flexibility for the left leg (R2=0.26). Discussion: The main findings of this study were 1) reliability was moderate for flexibility and low for strength, and 2) a decrease in flexibility was found as a result of match play. With regards to the first finding, it seems greater familiarisation is needed to improve strength test reliability. Despite no evidence of a linear correlation between match load and flexibility measures, it seems that there might be a match load threshold after which flexibility is negatively affected. However, this warrants further investigation using direct recording of match activity (e.g., distance) or physiological load (e.g., time x heart rate). In conclusion, given the time constraints and logistical issues surrounding strength testing, groin flexibility might be a sensitive and reliable measure to detect changes as a result of fatigue